Design and construction of a prototype resistive plate chamber - Yıldızcı, Zaynab Shahadad. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Resistive Plate Chambers (RPCs) are gaseous particle detectors that are used in various applications requiring coverage of large volumes with good time and position resolution, such as detection of muons in high-energy physics experiments. We present an overview of the basic literature on RPCs and describe the steps for realizing a mod est design with a very limited budget and without the need for a specialized equipment. The details, including information about the materials and their domestic availability as well as the knowhow to resolve encountered issues, are presented with the goal of establishing a baseline for future work on this area. The constructed RPC, which we believe is the ﬁrst of its kind in Turkey, has been tested with diﬀerent gases (argon and isobutane) and mixtures (air, argon-air, argon-isobutane). The test results and obser vations are also presented and their compatibility with the theoretical expectations is discussed.
Keywords: Particles (Nuclear physics)